2018
DOI: 10.2217/nnm-2017-0385
|View full text |Cite
|
Sign up to set email alerts
|

Silver Sulfadiazine Nanoethogel for Burn Healing: Characterization and Investigation of Its In Vivo Effects

Abstract: The SSD ethogels promotes the therapeutic effect of SSD for burn treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The concentration of DOX in the supernatant was measured by UV spectrophotometry (Varian, Cary 100 UV/Vis Spectrophotometer, USA) at 480 nm. The drug loading and encapsulation efficiency of DOX were calculated by the following formulas: 56 Drug loading contentð%Þ ¼ the weight of DOX in the nanoparticles the gross weight of the nanoparticles � 100…”
Section: Evaluation Of Encapsulation Efficiencymentioning
confidence: 99%
“…The concentration of DOX in the supernatant was measured by UV spectrophotometry (Varian, Cary 100 UV/Vis Spectrophotometer, USA) at 480 nm. The drug loading and encapsulation efficiency of DOX were calculated by the following formulas: 56 Drug loading contentð%Þ ¼ the weight of DOX in the nanoparticles the gross weight of the nanoparticles � 100…”
Section: Evaluation Of Encapsulation Efficiencymentioning
confidence: 99%
“…[27][28][29] Although topical silver sulfadiazine has been used in burn clinics as a potent antibacterial agent, it is not an antiinflammatory agent and its long-term use caused toxicity and impaired wound healing in burn patient and experiments as well. 19,30 In this study, the level of TGF-β1 cytokine production was less in ROCEN-treated group compared with zinc oxide group in injured tissue of rats after 7 days of topical application. Song et al showed that zinc oxide could protect the intestinal barrier via mitogen-activated protein kinases and TGF-β1 signaling pathways in weaned pigs.…”
Section: Discussionmentioning
confidence: 51%
“…[16][17][18] Recent studies presented the liposomal formulation as a promising tool in burn and wound therapy with no adverse effects on skin, which causes less drug toxicity as well as improvement of wound healing. 16,19,20 The goal of this study was to assess the effect of the liposome formulation of ASU (as named ROCEN) on burn wound healing in a second-degree burn model in rats. Also, the analgesic activity of ROCEN was evaluated by tail-flick and hotplate tests in which a heat stimulus was used to induce pain.…”
Section: Introductionmentioning
confidence: 99%
“…Razavi et al relied on ethosomal penetrating power and formulated (SSD) nanoethosomal gel using carbopol 974 as gelling agent [72]. SSD nanoethosomal gel was tested on rats with a second degree of burn.…”
Section: Ethosomesmentioning
confidence: 99%